Additions to Fitzroyomyces (Stictidaceae, Ascomycota) from Yunnan Province, China - Xu, Ruifang; Thiyagaraja, Vinodhini; Dai, Dong-Qin; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2022)
A total of approximately 104,000 fungal species can be expected in Yunnan. However, approximately 6000 fungal species have been reported from the province leaving much to be described. This study introduces a new species, Fitzroyomyces xishuangbannaensis sp. nov and a new collection of Fit. cyperacearum from Yunnan province, China. The taxa were characterized based on morphological characteristics and combined multi-gene phylogenetic analyses. Both maximum likelihood (ML) and Bayesian inference posterior probabilities (PP) were conducted for combined LSU, ITS and mtSSU sequences data. The new Fitzroyomyces species formed a distinct clade among the extant species of Fitzroyomyces with high statistical supports in the phylogenetic analyses while our new isolate nested together with the corresponding strains of Fit. cyperacearum. A key to Fitzroyomyces species and a synopsis table of morphological characteristics for Fitzroyomyces are provided to support the taxonomic placement.